EXAMINING THE IMPACT OF GROUP DISCUSSIONS ON PROMOTING GRAMMATICAL ACCURACY WITHIN A COMMUNICATIVE CONTEXT (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Effective communication involves not only conveying ideas but also expressing them with grammatical precision. In this context, group discussions play a pivotal role in fostering grammatical accuracy within a communicative setting. This article explores the profound impact of group discussions on language development, emphasizing how collaborative discourse enhances linguistic skills. One of the primary advantages of group discussions lies in the diverse perspectives that participants bring to the table. Within a communicative context, individuals are exposed to varied linguistic expressions, styles, and structures. As group members engage in conversations, they unconsciously correct each other's grammatical errors, contributing to a collective understanding of proper language usage. This collaborative learning process creates an environment where participants learn not just from instructors but also from their peers.